Evaluation of Climate-Smart Village roving workshop as a farmer-to-farmer learning platform - Trung, Nguyen Duc; Villanueva, Jerome; Khounthavong, Malisa; Eam, Dyna (2019)
In 2014, the CGIAR Research Program on Climate Change, Agriculture and Food Security in Southeast Asia (CCAFS SEA) established seven Climate-Smart Villages (CSVs) in the region. The CSVs are serving as models of climate-resilient communities and field laboratories of climate-smart agriculture (CSA) technologies and practices. In the following years, CCAFS SEA and various CGIAR Centers conducted studies and transferred a wide range of CSA technologies and practices in those villages. Farmer networks could ensure that these technologies and practices are fully adopted by the farmers. To establish these networks, capacity building activities such as CSV roving workshops can be organized. These workshops are held annually in different countries as a capacity building activity not only for farmers but also for local technical staff. These workshops were proved as effective communication channels, which directly provide information on CSA technologies and practices to the farmers; enhance their perception of innovation adaptability; and reduce the uncertainties about the risks and benefits of adoption. This working paper presents a brief overview of this learning method, the outputs, and initial outcomes from four roving workshops organized in Southeast Asia.